Multilocular cystic renal cell carcinoma in a 23 year old female - Shivakumarswamy Udasimath; J Niranjan; R Puruhotham; K R Nagesha (Urology Annals, 2016)
Multilocular cystic renal cell carcinoma (MCRCC) has been identified as a separate subtype of renal cell carcinoma (RCC) in the 2004 World Health Organization classification of adult renal tumors. MCRCC represents a rare variant of clear cell RCC. The common age group for this tumor is between 40 and 60 years. In our case, MCRCC occurred at the age of 23 years in a female patient. We report this case because of its rarity in this age group, sex, good prognosis, and also to avoid a misdiagnosis as conventional clear cell RCC. However, before making a diagnosis of MCRCC, it has to be differentiated from tubulocystic carcinoma, cystic nephroma, cystic clear cell carcinoma, and clear cell papillary RCC.